Physical and morphological characterisation of poly(L-lactide) acid-based electrospun fibrous structures: tunning solution properties. (26th November 2018) - Maleki, Homa; Semnani Rahbar, Rouhollah; Saadatmand, Mohammad Mahdi; Barani, Hossein
ABSTRACT: Poly(l-lactide) nano/micro fibres were produced using the electrospinning technique. The influence of solvent type and solution concentration on the morphology and structure of electrospun fibres were investigated. For this purpose, the electrospinning was performed using 2, 2, 2-trifluoroethanol (TFE) or dichloromethane (DCM) solvents at solution concentrations in a range of 5–9 wt-%. Morphological studies showed that versus DCM-based fibres with beaded structures and porous surface, when using TFE as a solvent, the uniform bead-free fibres with a smooth surface morphology were produced. Compared to DCM, the fibre diameter decreased using TFE as a solvent with lower vapour pressure while the crystallinity of the fibres increased. By increasing the solution concentration up to 9 wt-%, uniform fibres were produced with growing average diameters. Following these results, we conclude that varying the solution concentration and solvent type can modulate the final properties of electrospun fibres.